Looking at the Financial Performance of MSMEs: Do Financial Literacy, Fintech Lending, and the Effectiveness of Digital Payment Affect? - Rahayu, Nika Esti; Ibrahim, Rosida; Primasiwi, Asri; Azis, Abdul (PT Aksara Indo Rajawali, 2025)
The study aims to test the effect of financial literacy, fintech peer-to-peer lending, and digital payment on the financial performance of Micro, Small, and Medium Enterprises in Madiun City. The research method uses a quantitative approach with a sample of 394 MSME actors. The data analysis technique uses Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of the study indicate that financial literacy and fintech peer-to-peer lending have a positive effect on the financial performance of MSMEs. Meanwhile, digital payment does not affect the financial performance of MSMEs. The limitations of this study are that the sample and research variables are still limited. Despite the limitations, this study has practical implications as a reference for Micro, Small, and Medium Enterprises regarding the importance of financial literacy, fintech peer-to-peer lending, and the use of digital payments on financial performance.